Empowering rural women through Warung Nusa: A community-based tourism program in Denai Kuala - Salmina Wati Ginting; Arief Marizki Purba; Wahyuni Zahrah; Samerdanta Sinulingga (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang)
This community service program applies the Asset-Based Community Development (ABCD) approach to support the design and planning of Warung Nusa, a communal space in Denai Kuala Village, Deli Serdang, North Sumatera. As part of the Kampung Nusa initiative by HAPSARI and the development of Denai Kuala spice tourism village, this program aims to empower rural women through food security, entrepreneurship, and cultural revitalization. The method involved five ABCD stages: preparation, asset mapping, capacity building, implementation, and participatory evaluation. Local assets—such as women’s networks, household gardens, cultural stories, and the coastal landscape—were identified and mobilized to support the village’s transformation into a Spice Tourism Village (Desa Wisata Rempah). The main output was the co-design and construction of the green Warung Nusa, a communal kiosk made with locally sourced materials and designed for culinary tourism, cultural activities, and community gatherings. Results show increased community participation, enhanced women’s agency, and early economic impact through product sales and social events. The conclusion emphasizes that participatory planning and local asset mobilization are key to sustainable rural development. This program demonstrates how service-learning and design collaboration can build meaningful infrastructure while strengthening community capacity.